Pengaruh Ambulasi Dini terhadap Kejadian Konstipasi pada Ibu Postpartum - Lailatul Khusnul Rizki (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
Constipation is one of the problems during the initial parturition intimately connected with the early ambulation. In the village of Tanah Kalikedinding still turned out a lot of postpartum mothers who cannot yet CHAPTER more than three days. The purpose of this research is to know the influence of early ambulation with the incidence of constipation in the mother post, in the village of Tanah Kalike dinding Surabaya. This type of analytical research with cross sectional approach, its population is the entire mother childbirth > 3 days in the village of Tanah Kalikedinding as much as 28 people. A large sample of 26 respondents taken in "simple random sampling". random sampling source this research obtained from the questionnaire. The independent variable is the dependent variable, while the early ambulation is the incidence of constipation. Analysis using Fisher Test with α = 0,05. The results showed that out of the 26 respondents obtained most of the 15 (57,7%) of respondents experiencing constipation. Test statistic chi-square obtained with 2 cells (50%) EF < 5. Therefore do exact test values obtained by exact fisherand P = 1 and a = 0,05 it means P >athe table then H0 is accepted means there's no intercourse means there is no influence of early ambulation with the incidence of constipation in the mother post. Summary of the research is there is no influenceof early ambulation with the incidence of constipation on postpartum mothers. We recommend that health workers should provide counseling for prevent constipation